If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(v + 4) + 2v + 6 = 5v + 7 Reorder the terms: -9(4 + v) + 2v + 6 = 5v + 7 (4 * -9 + v * -9) + 2v + 6 = 5v + 7 (-36 + -9v) + 2v + 6 = 5v + 7 Reorder the terms: -36 + 6 + -9v + 2v = 5v + 7 Combine like terms: -36 + 6 = -30 -30 + -9v + 2v = 5v + 7 Combine like terms: -9v + 2v = -7v -30 + -7v = 5v + 7 Reorder the terms: -30 + -7v = 7 + 5v Solving -30 + -7v = 7 + 5v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-5v' to each side of the equation. -30 + -7v + -5v = 7 + 5v + -5v Combine like terms: -7v + -5v = -12v -30 + -12v = 7 + 5v + -5v Combine like terms: 5v + -5v = 0 -30 + -12v = 7 + 0 -30 + -12v = 7 Add '30' to each side of the equation. -30 + 30 + -12v = 7 + 30 Combine like terms: -30 + 30 = 0 0 + -12v = 7 + 30 -12v = 7 + 30 Combine like terms: 7 + 30 = 37 -12v = 37 Divide each side by '-12'. v = -3.083333333 Simplifying v = -3.083333333
| 8a-4=12 | | 3p+4b=3.75 | | 4x+7y=39 | | 7x+3+2x-x=1 | | 125+12x=725 | | 5(3x+6)=6-(x+8) | | -7p-3(6-4p)=2(p-6)-18 | | -6x+28=-2-7(6+6x) | | 8(2x-5)=40 | | 13.9+v=18.3 | | 14x^2+49x-273=0 | | 4x+32-1x=64 | | 6(v+3)-2v=2(2v+2)-7 | | 5a-10=5 | | .2x+6=31 | | (9n-1)+7(n+6)=-60 | | 3x^2-xy-52y^2=0 | | 3x+2x+7=-41 | | -27=2c-7c-6c | | 3x+1=3x-8 | | 15x+45=120 | | 6(2t-5)=60-6t | | 1/2=3/3 | | 3.75x=21 | | 5x+4x=7 | | 2x-10y=10 | | k=25 | | 16w^2-70w+49=0 | | t+9-3.2=3 | | 8c-72=8c-72 | | 5t+16=11t+4 | | 8x-2=20x+4 |